Brassica carinata and Brassica napus Growth, Nitrogen Use, Seed, and Oil Productivity Constrained by Post‐Bolting Nitrogen Deficiency. Issue 6 (1st November 2019) - Seepaul, Ramdeo; Small, Ian M.; Marois, Jim; George, Sheeja; Wright, David L.
ABSTRACT: Nitrogen limitation after bolting in oilseed brassicas limits reproductive performance as nutrients are sequentially translocated from leaves to developing reproductive structures. In addition to limiting crop growth and productivity, N deficiency may also modify the chemical composition and oil output of Brassica carinata A. Braun and B. napus L. A greenhouse study was conducted at the North Florida Research and Education Center in Quincy, FL, during 2014–2015 to determine the effects of N limitation on B. carinata (cultivar AAC A110) and B. napus (cultivar Canterra 1918) growth, seed and oil yields, N use, and fatty acid composition. Four N treatments (0, 33, 66, and 100% of N in full strength Hoagland solution) were imposed 78 d after planting (DAP) at bolting. At 154 DAP, carinata accumulated 19% greater biomass and nine times more reproductive branches than napus across all N levels. As a result, carinata produced 43% greater seed yield across all N levels than napus. This increased seed productivity resulted in greater agronomic efficiency (58%), apparent N recovery (59%), N utilization efficiency (41%), and partial factor productivity (29%) than napus, respectively. Restricting N availability (0 N) reduced carinata and napus oil yield by 35 and 50% respectively, relative to 100% N. Nitrogen availability during seed development and maturation had an effect on the synthesis of fatty acids and their quantities in the oils of mature carinata and napus seeds. This study demonstrated the plasticity of oilseed brassicas and the relationship of reduced growth to seed productivity as a function of N supply.